Recombination at oxide precipitates in silicon - Murphy, J; Bothe, K; Krain, R; Olmo, M; Voronkov, V; Falster, R (Trans Tech Publications Ltd, 2011)
Transient and quasi-steady-state photoconductance methods were used to measure minority carrier lifetime in p-type Czochralski silicon processed in very clean conditions to contain oxide precipitates. Precipitation treatments were varied to produce a matrix of samples, which were then characterised by chemical etching and transmission electron microscopy to determine the density and morphology of the precipitates. The lifetime component associated with the precipitates was isolated by preventing or factoring out the effects of other known recombination mechanisms. The lifetime component due to unstrained precipitates could be extremely high (up to ∼4.5ms). Recombination at unstrained precipitates was found to be weak, with a capture coefficient of ∼8 × 10-8cm3s-1 at an injection level equal to half the doping level. Strained precipitates and defects associated with them (dislocations and stacking faults) act as much stronger recombination centres with a capture coefficient of ∼3 × 10-6cm 3s-1 at the same level of injection. The lifetime associated with strained precipitates increases with temperature with a ∼0.18eV activation energy over the room temperature to 140°C range. The shape of the injection level dependence of lifetime was similar for all the specimens studied, with the magnitude of the lifetime being dependent on the precipitate density, strain state and temperature, but independent of precipitate size. © (2011) Trans Tech Publications, Switzerland.